Seeing Double - Larsen, Jens Kristian (Plato Journal, 2021)
In a crucial passage in the Republic (454a1-8) found within a discussion of women’s role in the ideal polis, division of eidē is identified as necessary for dialectic. A careful consideration of the way division is described in this passage reveals that it resembles the procedure of division described in the Phaedrus and the Sophist and that this procedure, when carried out correctly, is central to dialectic according to the Republic and helps set dialectic apart from eristic. Consideration of additional passages in the Republic indicates that division may be employed on different kinds of entities, such as virtues and types of human natures; for according to the argument of the Republic, the correct use of division for the purpose of distinguishing types of human natures or virtues, entities that to the untrained eye may look alike but are distinct by nature, is required for achieving the knowledge philosophers and philosopher-rulers need. In fact, correctly performed divisions help the dialectician to bring into focus a subject matter under consideration in a kind of double-vision that reveals that matter as a concrete phenomenon that exhibits participation in different eidê when it is considered from different points of view.